DECONTAMINATION DES SOLS POLLUES PAR LES HYDROCARBURES DECONTAMINATION OF SOILS POLLUTED BY HYDROCARBONS - HICHAM RHBAL; SALAH SOUABI; MOHAMED SAFI; MOHAMED TERTA; MOHAMED ARAD; ABDELKADER ANOUZLA; MOHAMED HAFIDI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Bioremediation is a viable process used to treat contaminated lands by hydrocarbons. It can be improved by the use of organic waste. The overall study objective was the evaluation of the impact of an organic substrate (active sludge) in decontaminating petroleum hydrocarbons polluted sites through the composting system. As a result, both wastes from petroleum refinery and industrial sources (hydrocarbon polluted sites and the activated sludge) are mixed at different percentages B, C, D, (soil/activated sludge 6/4, 7/3, 8/2) respectively in addition to a control system A (100 % soil). The physic-chemical parameters are controlled in order to assure that the composting process is running correctly. The study has shown that bioremediation via composting process is very efficient at reducing the concentration of pollutants and evaluating organic wastes that are high in nutritional elements. The composting process can be thus considered as a means of solid waste management.